Capturing spatially resolved kinetic data and coking of Ga–Pt supported catalytically active liquid metal solutions during propane dehydrogenation in situ. (5th March 2021) - Wolf, Moritz; Raman, Narayanan; Taccardi, Nicola; Horn, Raimund; Haumann, Marco; Wasserscheid, Peter
Abstract : Spatially resolved kinetic data of gallium–platinum SCALMS was captured while elucidating the effect of carrier material on coke formation. Abstract : Supported liquid phase catalysis has great potential to unify the advantages from both homogeneous and heterogeneous catalysis. Recently, we reported supported catalytically active liquid metal solutions (SCALMS) as a new class of liquid phase catalysts. SCALMS enable high temperature application due to the high thermal stability of liquid metals when compared to supported molten salts or ionic liquids. The highly dynamic liquid metal/gas interface of SCALMS allows for catalysis over single atoms of an active metal atom within a matrix of liquid gallium. In the present study, kinetic data is acquired along the catalyst bed in a compact profile reactor during propane dehydrogenation (PDH) over gallium–platinum SCALMS. The reactor design allows for the analysis of the temperature and gas phase composition along the catalyst bed with a high spatial resolution using a sampling capillary inside the reactor. The concentration profiles suggest enhanced deactivation of the catalyst at the end of the bed with a deactivation front moving from the end to the beginning of the catalyst bed over time on stream. Only minor amounts of side products, formed via cracking of propane, were identified, supporting previously reported high selectivity of SCALMS during alkane dehydrogenation. The acquired data is supported by in situ high-resolution thermogravimetry coupled with mass spectrometry to monitor the activity and coking behaviour of SCALMS during PDH. The results strongly suggest an enhanced formation of coke over Al2 O3 -supported SCALMS when compared to using SiO2 as the support material.